(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In present era vast development occurred in the field of concrete technology. Many scientists and researchers have been developed abundant techniques to improve strength and durability parameters of the concrete. A number of studies have been carried out to investigate the possibility of utilizing a broad range of materials as partial replacement material for cement in the production of concrete. The use of supplementary cementations material in production of concrete can result in major saving of energy and cost. It also helps to improve strength, durability, and chemical resistance of concrete.Use of admixtures has been a costly affair in concrete mix. Though it enhances the properties of the final product the cost incurred is not optimum. Every production industry produces some by-products which may not be useful for them in the future and are termed as waste products. One such waste that is generated in Sugar industries is molasses. It is generally the waste floating on the sugar juice during the production of sugar from sugarcane. Being cheaper in cost it can widely be used as an admixtures. This study has found that use of molasses as an admixture enhances the properties of concrete such as initial and final setting time, strength and workability. In this study a comparison between concrete with 3, 4 and 5 of molasses addition with constant water cement ratio is done. Molasses obtained from sugar industries have been used for the experimental purpose. Workability is carried out at initial fresh concrete stage. Compressive strength, Split tensile strength and flexural strength is carried out on hardened concrete. Strength characteristics are tested on 3rd day, 7th day and 28th day of casting of concrete Keywords Concrete, strength, molasses, cost, workability, admixtures.